Development of the Hypothalamic Melanocortin System - Coupe, Berengere; Bouret, Sebastien G. (Frontiers in Endocrinology, 2013)
The melanocortin system is a critical component of the forebrain and hindbrain regulatory systems involved in energy balance. This system is composed of pro-opiomelanocortin (POMC) neurons that act, in part, through the melanocortin-4 receptor (MC4R). Although the importance of the melanocortin system in controlling feeding has been established for two decades, the understanding of the developmental substrates underlying POMC and MC4R neuron development and function has just begun to emerge. The formation of the melanocortin system involves several discrete developmental steps that include the birth and fate specification of POMC- and MC4R-containing neurons and the extension and guidance of POMC axons to their MC4R-expressing target nuclei. Each of these developmental processes appears to require specific sets of genes and developmental cues that include perinatal hormones. Recent evidence has also highlighted the importance of perinatal nutrition in controlling the ultimate architecture of the melanocortin system.